Using chlorhexidine varnish to prevent early childhood caries in American Indian children. (26th June 2012) - Robertson, Lawrence D.; Phipps, Kathy R.; Oh, Junhie; Loesche, Walter J.; Kaciroti, Niko; Symington, John M.
Abstract Objectives: To test the efficacy of 10% chlorhexidine (CHX) dental varnish applied to the mothers' dentition in preventing caries in American Indian children. Methods: This was a placebo‐controlled, double‐blind, randomized clinical trial. Mother–child pairs were enrolled when the child was 4.5‐6.0 months. Mothers received 4 weekly applications of the study treatment (CHX or placebo) followed by single applications when her child was age 12 and 18 months. Children received caries examinations at enrollment, 12, 18 and 24 months. Analyses were limited to the intent‐to‐treat (ITT) group: children whose mothers received the first study treatment and who received at least one post‐baseline exam. The outcome variable was the number of new carious surfaces (NNCS) at the child's last visit. Wilcoxon nonparametric and Fisher's exact tests were used to test differences between the active and placebo groups. Results: We randomized 414 mother–child pairs, with 367 (88.6%) included in the ITT group (active = 188, placebo = 179). The proportion of children caries‐free at their final exam was 51.1% and 50.8% for the active and placebo groups (P > 0.99). The mean NNCS for the active and placebo groups was 3.82 (standard deviation [SD] = 8.18) and 3.80 (SD = 6.08), respectively (P = 0.54). The proportion with NNCS > 6 was 18.1% for active children versus 27.9% for placebo (relative risk [RR] = 0.65, P = 0.03). The number needed to treat to shift one child from NNCS > 6 to a lower severity was 10.2. Conclusions: In this population CHX varnish did not reduce the mean NNCS or proportion of children with caries, but did reduce the proportion with severe caries.